ANALYSIS OF E-ARRIVAL CARD SYSTEM WITH COBIT 5 FRAMEWORK IN THE DELIVER, SERVICE, SUPPORT (DSS) DOMAIN - W Wilonotomo; Wahyu Eka Putra; Dedi Muhaemin (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
E-arrival card is an electronic arrival card that is used to collect data on foreigners entering Indonesia. Bandung Immigration Office Class I of Border Control is one of the Immigration Offices in West Java that has implemented an electronic arrival card called IDN E-Arrival Card Jabar. Every foreign citizen who enters Indonesia through the Immigration Checkpoint of Husein Sastranegara International Airport is required to fill in data on the e-arrival card system. This e-arrival card system must run with maximum and optimal conditions, therefore an analysis system is needed to determine the service performance and security of the e-arrival card system by carrying out an audit process. The audit process using the COBIT 5 framework. The purpose of this study is to measure the capability level of the e-arrival card system and provide recommendations and suggestions regarding the results of measuring the capability level of the e-arrival card system using the COBIT 5 framework in the DSS (Deliver, Service, Support) domain. The research method used is qualitative using the COBIT 5 framework. The results obtained regarding the measurement of capability level on the e-arrival card system with the COBIT 5 framework in DSS01 (manage operations) are at level 4 is predictable process, for DSS02 (Manage service requests and incidents), DSS03 (Manage problems), DSS04 (Manage continuity), DSS05 (Manage security services) and DSS06 (Manage business process controls) are each at level 3 is established process. Recommendations that can be given are to carry out periodic maintenance and evaluation as well as to make standard operating procedures (SOP) for services and incidents regarding the e-arrival card system.